Evolution Characteristics of Pore–Fractures and Mechanical Response of Dehydrated Lignite Based on In Situ Computed Tomography (CT) Scanning - Shuai Yan; Lijun Han; Shasha Zhang; Weisheng Zhao; Lingdong Meng (Fractal and Fractional)
Based on the uniaxial compression tests and in situ CT scanning experiments of lignite with different dehydration times and the fractal theory, this paper qualitatively and quantitatively investigated the influence of the dehydration effect on the evolution of pore–fractures and the mechanical behavior of lignite under uniaxial compression conditions. The results show that the dehydration effect significantly affects the pre-peak deformation and post-peak failure behavior of lignite but has no significant impact on its peak strength. The pore–fracture parameters, such as the fractal dimension, surface porosity, and fracture volume, of three samples all exhibit an evolutionary pattern of “continuous decrease in the compaction and elastic stages–gradual increase in the plastic stage–sharp growth in the post-peak stage” with the dynamic evolution of the pore–fractures. However, the dehydration effect leads to an increase in the intensity of pore–crack evolution and a nonlinear rise in all the parameters characterizing the pore–crack complexity during uniaxial compression, which, in turn, leads to an increment in the fluctuation of the above evolutionary trends. The mechanism underlying the differential influence of the dehydration effect on the macroscopic mechanical behavior of lignite is follows: The dehydration effect non-linearly and positively affects the initial pore–fracture structure of lignite, thereby non-linearly and positively promoting the evolution of pore–fractures during the loading process. Nevertheless, since it fails to weaken the micro-mechanical properties of lignite and cannot form effective through-going fractures, it has no significant impact on the uniaxial compressive strength of the coal samples. The findings of this study can provide some references for the support design and deformation control of underground lignite roadways.